Minor criteria for atopic dermatitis in children - Wahab, MA; Rahman, MH; Khondker, L; Hawlader, AR; Ali, A; Hafiz, MA; Ansari, NP (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):419-424 The abstract of this article is available on the PubMed website